Edifici di culto e inter-culturalità (il caso spagnolo della Moschea-Cattedrale di Cordova (Stato, Chiese e pluralismo confessionale, 2017)
SOMMARIO: 1. Premessa: un percorso in terra infidelium, ossia un’indagine su un campo, per chi scrive, pressoché inesplorato - 2. Profili teologici: la “relativizzazione” degli edifici di culto - 3. Profili giuridico-canonistici: la “valorizzazione” degli edifici di culto - 4. Cenni sulla situazione dei beni ecclesiastici, e segnatamente degli edifici di culto, in Italia - 5. Il singolare caso spagnolo della Cattedrale di Cordova - 6. Profili ecclesiasticistico-costituzionali: la “doppia natura” della Mezquita, come “Cattedrale cattolica” e come bene “inter-culturale”, dunque, potenzialmente, inter-confessionale … - 7. (segue): “resistenze” nel dialogo inter-religioso. Casi simili o analoghi - 8. Conclusioni: necessità di soluzioni consensuali, forse “imperfette”, ma costituzionalmente ragionevoli.Worship Buildings And Interculturality (The Spanish case of the Mosque-Cathedral of Cordoba)ABSTRACT:After a brief exposition of theological and legal aspects (canon law) of worship buildings, also with reference to Italy, the paper focuses on Spanish system and the peculiar case of Cordoba Cathedral. From an ecclesiastical-constitutional law perspective, the Mosque has a “double essence”: “catholic cathedral” and “intercultural good”, with a potential interfaith meaning. Thus, none of the following solutions can be accepted: 1) expropriate and change the temple in a public lay museum (irritating both Christian and Islamic communities); 2) qualifying again the temple as a Mosque (after 8 centuries of Christian worship); 3) leaving it solely as a Cathedral (despite its original architecture as a Mosque); 4) make of it an interfaith temple (with the risk of syncretism). The paper suggests that a solution by an agreement between the two groups, however imperfect, is possible (and reasonable from a constitutional perspective): a partial “sharing” of the building, in a brotherhood spirit of high symbolic meaning.
Keywords: Edifici ed edilizia di culto